ANTIBIOTIC RESISTANCE OF MICROORGANISMS ISOLATED FROM PATIENTS OF SURGICAL HOSPITAL - E. V. Anganova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
Infections received in the course of healthcare delivery continue to be an urgent medical and socio-economical issue. This problem is exacerbated by formation and wide spread of strains polyresistant to current germicides. The article presents the results of a study of antibiotic resistance of microorganisms isolated from patients of surgical hospital of Neryungri Central Regional Hospital. Microorganisms were resistant to various antimicrobial drugs. E. coli were resistant to ampicillinum, ampicillinum/sulbactam and ceftriaxonum; Klebsiella spp. - to ampisiillinum, chloramphenicolum and cefotaxime; Pseudomonas aeruginosa - to ciprofloxacinum and gentamicinum, Acinetobacter spp. - gentamicinum, ceftazidime and ceftriaxonum; Staphylococcus - to penicillinum. Escherichia coli and Klebsiella spp. produced extended spectrum beta-lactamases (ESBL). Among E. coli, Pseudomonas aeruginosa and Acinetobacter spp. were identified strains resistant to carbapenems. MRSA and MRSE were identified.